Process of parturition in buffaloes - MODI, MUKESH; CHAUHAN, R A S; SHUKLA, S P (The Indian Journal of Animal Reproduction, 2023)
The present investigation was carried out on 15 parous she buffaloes maintained by farmers in the ruralarea around Mhow. The dilation of cervix., expulsion of fetus and the expulsion of fetal membranes required a meanduration of31.60±3.07, 43.59±5.25 and 429.33±43.84 minutes, respectively. The mean duration for the whole act ofparturition was recorded as 504.52±45.97 minutes. In all cases, allantochorion appeared as the first water bag. Thefetuses were found in anterior longitudinal presentation and dorsosacral position with head resting on forelimbs.Maximum number of calvings (80%) occurred during night hours ( 6 p.m. to 6 a.m. ).
Keywords: Foetal membranes; panuririon; buffaloes